Health Issues Among Healthcare Workers During COVID-19 Pandemic: a Psychosomatic Approach - Felix F Widjaja; Hamzah Shatri; Rudi Putranto (Acta Medica Indonesiana, 2020)
Healthcare workers as the front-liner to fight COVID-19 pandemic, need reassurance of their safety. The stress and the demands from the healthcare system can affect their health as well as the morality. Hence, psychosomatic approach should be used to keep their condition in good shape. The combination between biological, psychological, and social approaches may affect their vulnerability from SARS-CoV-2 infection. The biological aspect includes personal protective equipment, nutrition, and resting/sleeping time. The psychological distress is shown to affect the immune system; and mental relaxation and management of work shift may reduce the distress. There should be an effort from the stakeholders to keep the morality of the healthcare workers. The social aspect such as providing place to live, having supportive family members, and avoiding stigmatization also improve their psychological health. In conclusion, psychosomatic approach is important to keep the healthcare workers healthy.